2023
DOI: 10.1093/emph/eoad001
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity, diet and mental distress among resource insecure students during COVID-19

Abstract: It is well documented that college student populations are vulnerable to food insecurity and other adverse environmental conditions. Additionally, exposure to environmental adversity can have deleterious, long-term effects on physical and mental health. This study applies evolutionary life history theory to examine the relationship between environmental adversity, mental distress, and diet among resource insecure university students during the COVID-19 pandemic. Structured and semi-structured surveys were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Indeed, Roulette and Kopels (2023) found that current levels of FI are linked with perceptions of extrinsic mortality risk among economically vulnerable college students. In addition, among a sample of U.S. students, FI and extrinsic mortality risk are associated with greater mental distress (Kopels & Roulette, 2023), and less self‐reported effort put forth to maintain long‐term economic well‐being (Roulette & Kopels, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Roulette and Kopels (2023) found that current levels of FI are linked with perceptions of extrinsic mortality risk among economically vulnerable college students. In addition, among a sample of U.S. students, FI and extrinsic mortality risk are associated with greater mental distress (Kopels & Roulette, 2023), and less self‐reported effort put forth to maintain long‐term economic well‐being (Roulette & Kopels, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been documented across several studies, which show that FI students are more vulnerable to sleep issues, such as: (1) trouble falling asleep and staying asleep (Nagata et al, 2019), (2) fewer days with enough sleep (Martinez et al, 2019), and (3) daytime fatigue or sleepiness (Becerra et al, 2020). Alongside poor sleep, studies link FI to deleterious mental health, specifically: anxiety (Nagata et al, 2019), depression (Payne‐Sturges et al, 2018), psychological distress (Becerra et al, 2020; Kopels & Roulette, 2023), and suicidal ideation (Nagata et al, 2019). Taken together, this strongly suggests that FI college students are a vulnerable population more likely to experience poor sleep and mental health issues that put long‐term health at risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less is known about food insecurity and decreased intake of fruits and vegetables within health professional students. 30 Exercise frequency and type. Physical activity is essential to improve and/or maintain physical and mental health and enhance quality of life.…”
Section: Substance Usementioning
confidence: 99%
“…Additionally many family members including parents have lost their employment or are facing pay cuts in the wake of this pandemic (Prior, de Heer, & Maas, 2023;Son, Hegde, Smith, Wang, & Sasangohar, 2020). A study also reported that financial insecurity and prolonged joblessness are strongly related with increased rates of mental distress among university students (Khoury-Malhame, Rizk, Joukayem, Rechdan, & Sawma, 2023;Kopels & Roulette, 2023;Salman et al, 2022). Moreover, having chronically ill family members (parents or relatives) also raised their distress (S€ og€ ut, Dolu, & Cang€ ol, 2021) and added to financial burden.…”
Section: Introductionmentioning
confidence: 99%